2014
DOI: 10.1073/pnas.1400150111
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3A Arg882 mutation drives chronic myelomonocytic leukemia through disturbing gene expression/DNA methylation in hematopoietic cells

Abstract: The gene encoding DNA methyltransferase 3A (DNMT3A) is mutated in ∼20% of acute myeloid leukemia cases, with Arg882 (R882) as the hotspot. Here, we addressed the transformation ability of the DNMT3A-Arg882His (R882H) mutant by using a retroviral transduction and bone marrow transplantation (BMT) approach and found that the mutant gene can induce aberrant proliferation of hematopoietic stem/progenitor cells. At 12 mo post-BMT, all mice developed chronic myelomonocytic leukemia with thrombocytosis. RNA microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 36 publications
1
70
1
Order By: Relevance
“…The importance of DNMT3A in hematopoiesis and leukemogenesis has been demonstrated by studies using Dnmt3a knockout or DNMT3A R882-overexpressing mice (7,12,22). In this study, the conditional knockin mouse model allowed the inducible allelic switch from Dnmt3a WT/WT to Dnmt3a R878H/WT in the hematopoietic system of adult animals, which indeed possessed some major features of human AML associated with the DNMT3A mutation.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The importance of DNMT3A in hematopoiesis and leukemogenesis has been demonstrated by studies using Dnmt3a knockout or DNMT3A R882-overexpressing mice (7,12,22). In this study, the conditional knockin mouse model allowed the inducible allelic switch from Dnmt3a WT/WT to Dnmt3a R878H/WT in the hematopoietic system of adult animals, which indeed possessed some major features of human AML associated with the DNMT3A mutation.…”
Section: Discussionmentioning
confidence: 86%
“…This kind of DNMT3A mutation confers reduced methyltransferase activity and promotes the possibility of dominant-negative consequences compared with the wild-type (WT) allele (2,9,10). Moreover, the DNMT3A mutation causes aberrant DNA hypomethylation and up-regulates a series of target genes involved in AML pathogenesis (11)(12)(13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo analysis using a retroviral transduction of DNMT3A R882H mutant construct and bone marrow transplantation (BMT) assay showed development of chronic myelomonocytic leukemia (CMML)-like disease in mutant recipients, possibly through increased CDK1 protein level and enhanced cell-cycle activity [30]. Similarly, mice transplanted with Dnmt3a-null whole bone marrow (BM) or HSCs developed a spectrum of hematologic malignancies, including MDS, AML, myeloproliferative neoplasms (MPN), and T-and B-cell acute lymphocytic leukemia (ALL) [31,32].…”
Section: Dnmt3amentioning
confidence: 99%
“…Intriguingly, heterozygous mutations are most common with recent data demonstrating that R882 DNMT3A mutations have a dominant negative effect through inhibition of DNMT3A oligomerization. [35][36][37] DNMT3A mutations have also been identified in patients with myelodysplastic syndromes (MDS) 38 and myeloproliferative neoplasms (MPN), 39 and are associated with increased likelihood of progression to AML. Indeed, in some studies, the same DNMT3A mutation as the antecedent hematologic disorder is identified in secondary AML, suggesting that these mutations may be an early event in malignant clonal evolution.…”
Section: Dna Methyltransferase Enzymesmentioning
confidence: 99%